2014
DOI: 10.1093/jae/eju017
|View full text |Cite
|
Sign up to set email alerts
|

Positional Concerns among the Poor: Does Reference Group Matter? Evidence from Survey Experiments

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…This result is also similar to the finding obtained by Celse () about praise from supervisors. Moreover, in order to compare our findings with previous studies in countries whose culture focused on collectivism (e.g., Solnick et al ., ; Carlsson and Qin, ; Akay et al ., ), let us focus on income, which is the only domain these studies share. While Solnick et al .…”
Section: Resultssupporting
confidence: 41%
See 4 more Smart Citations
“…This result is also similar to the finding obtained by Celse () about praise from supervisors. Moreover, in order to compare our findings with previous studies in countries whose culture focused on collectivism (e.g., Solnick et al ., ; Carlsson and Qin, ; Akay et al ., ), let us focus on income, which is the only domain these studies share. While Solnick et al .…”
Section: Resultssupporting
confidence: 41%
“…This result is also similar to the finding obtained by Celse (2012) about praise from supervisors. Moreover, in order to compare our findings with previous studies in countries whose culture focused on collectivism (e.g., Solnick et al, 2007;Carlsson and Qin, 2010;Akay et al, 2014), let us focus on income, which is the only domain these studies share. While Solnick et al (2007) and Carlsson and Qin (2010) found that more than 50% of their Chinese respondents picked the positional situation, between 25% and 29% of individuals in our sample did so.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations